Symptom networks in major depressive disorder and treatment response: special focus on TRD - Alexander Kautzky; Lucie Bartova; Markus Dold; Daniel Souery; Stuart Montgomery; Joseph Zohar; Julien Mendlewicz; Chiara Fabbri; Alessandro Serretti; Evgenii Tretiakov; Dan Rujescu; Tibor Harkany; et al. (European Psychiatry)
Abstract Background Heterogeneous symptoms in major depression contribute to unsuccessful antidepressant treatment, termed treatment-resistant depression (TRD). Psychometric network modeling conceptualizes depression as interplay of symptoms with potential benefits for treatment; however, a knowledge gap exists regarding networks in TRD.